Space exploration and lifestyle medicine: a narrative review of its implications for astronaut health and remote Earth-based environments - Giguère, Raphaëlle; Marois, Alexandre; Fortin-Guichard, Daniel; Charest, Jonathan; Rocheleau, Julie; Thompson, Keith; Stolberg, Michael; St-Martin, Philippe; Bergouignan, Audrey; Niaussat, Victor; Paquette, Jean-Sébastien; Gagnon, Marie-Pierre; et al. (Frontiers in Physiology, 2026)
BackgroundSpace exploration, especially long-duration missions such as those to Mars, presents unique and significant challenges to astronaut health. Space medicine, which focuses on maintaining health in extreme environments without access to definitive medical care, emphasizes preventive measures. Lifestyle medicine (LM), grounded in six pillars such as healthy nutrition, regular physical activity, restorative sleep, stress management, positive social connections, and avoidance of risky substances, has proven effective for disease prevention on Earth. However, its application to spaceflight and remote Earth environments remains underexplored. This raises the question of how LM framework can sustain astronaut health and inform preventive and primary care strategies for remote Earth populations.ObjectiveThis narrative review examines how LM can support astronaut health during long-duration missions and draws parallels with healthcare needs in remote Earth populations. It establishes principles for integrating lifestyle and space medicine and provides recommendations for their application in both contexts.ResultsEach LM pillar is uniquely challenged in space. Nutritional constraints arise from limited food variety and storage capacity; microgravity and workload restrictions limit physical activity; circadian disruption and environmental noise affect sleep; isolation, confinement, and mission stress compromise stress regulation and social connections; restricted crew size and communication delays limit social connection; and strict medication policies highlight the dual role of substance use as both risks and necessity. While individual countermeasures have been tested in space, no integrated framework addressing all pillars simultaneously has yet been implemented. Technological innovations, such as wearable devices for continuous monitoring, telehealth modules for remote support, and virtual reality platforms for mental health and social engagement, appear as promising enablers of such an integrated approach for both astronauts and populations in medically underserved areas on Earth.ConclusionLM provides a preventive framework that complements traditional countermeasure and may enhance resilience and autonomy during space missions. Future research should prioritize integrated, longitudinal studies in analog environments to quantify the synergistic effects of integrated LM interventions versus single pillar countermeasures. Its translation to remote and underserved populations on Earth could help reduce healthcare disparities and support scalable, autonomy-centered models of care, underscoring the bidirectional value of combining lifestyle and space medicine.